Evaluación técnico-financiera de diferentes prácticas de perforación para la reducción del impacto que generan las pérdidas de circulación en Campo Castilla campaña 2015-2018 (2019)
Initially the root cause is identified and the transcendence of the losses of circulation in the field is taken into account, with this a technical financial analysis of different practices that were implemented to remedy the circulation losses among which were studied: management control pressure, blind drilling, implementation of LCM and other technologies, which are held throughout the drilling of the wells of the campaign, analyzed in how many wells were implemented, number of pills, cement plugs, among others and its result in each well, in order to identify through a selection and comparative matrix, which practice yields the best result throughout the campaign, its economic impact is also evaluated using the VPN methodology.